Peripheral Vascular Intervention: A Review (Bangladesh Heart Journal, 2019)
The prevalence of peripheral artery disease (PAD) continues to increase worldwide. It is important to identify patients with PAD because of the increased risk of myocardial infarction, stroke, and cardiovascular death and impaired quality of life because of a profound limitation in exercise performance.Lower extremity PAD affects approximately 10% of population, with 30% to 40% of these patients presenting with claudication symptoms. Peripheral arterial disease is common, but the diagnosis frequently is overlooked because of subtle physical findings and lack of classic symptoms. Screening based on the ankle brachial index using doppler ultrasonography may be more useful than physical examination alone. Noninvasive modalities to locate lesions include duplex scanning, computed tomography angiogram, magnetic resonance angiography and invasive modalities peripheral angiogram is the gold standard. Major risk factors for peripheral arterial disease are cigarette smoking, diabetes mellitus, older age (older than 40 years), hypertension, hyperlipidemia, and hyperhomocystinemia. Intermittent claudication may be improved by risk-factor modification, exercise, and pharmacologic therapy. Based on available evidence, a supervised exercise program is the most effective treatment. Effective drug therapies for peripheral arterial disease include aspirin (with or without dipyridamole), clopidogrel, cilostazol, and pentoxifylline. By contrast, critical limb ischemia (CLI) is considered the most severe pattern of peripheral artery disease. It is defined by the presence of chronic ischemic rest pain, ulceration or gangrene attributable to the occlusion of peripheral arterial vessels. It is associated with a high risk of major amputation, cardiovascular events and death. The management of CLI should include an exercise program, guideline-based medical therapy to lower the cardiovascular risk. Most of the cases, revascularization is indicated to save limbs; an “endovascular first” approach and lastly surgical approach, if all measures were failed. The choice of the intervention is dependent on the anatomy of the stenotic or occlusive lesion; percutaneous interventions are appropriate when the lesion is focal and short but longer lesions must be treated with surgical revascularisation to achieve acceptable long-term outcome.Bangladesh Heart Journal 2019; 34(1) : 58-67